PENGARUH SUPERVISI AKADEMIK DAN MOTIVASI KERJA KEPALA SEKOLAH TERHADAP DISIPLIN KERJA GURU SD - Burhan Burhan; Uray Husna Asmara; Aswandi Aswandi (Universitas Tanjungpura, 2017)
AbstractThis research aim to know the influence supervise the academic and motivate the headmaster job to discipline work the elementary schoolteacher in subdistrict of Jawai of South arch of regency Sambas. Approach used by is quantitative approach with the study corelational. Research data of about supervision academic ( Variable X1), motivate the headmaster job( Variable X2), and discipline work the teacher (Variable Y) collected by through/ passing enquette spreading to responder by using technique of proportional random sampling.Result of research indicate that the supervision academic show the result which significan with the discipline work the teacher that is reach 42,5%. Though do not show the dominant result but supervise this academic of vital importance so that teacher can realize the attainer of study target. And so do the things of with the motivation work the headmaster, result of from research got by Beta ( b1) of equal to 0,388 = 38,8%, the result show the existence of influence which significan with the discipline work the teacher. While influence supervise the academic ( X1) and motivate the headmaster job ( X2) by together with discipline work the teacher ( Visible Y) from R2 ( R Square) equal to 0,723 or 72,3%. This matter indicate that the independent variable relation link percentag (supervise the academic and motivate the headmaster job) with the variable dependent (discipline work the teacher) equal to 72,3%. Keyword : Supervise The Academic, Motivate The Headmaster Job, Discipline Work Teacher